The parallel operation control of a modular AC to DC converter via serial communication bus. Issue 1 (28th November 2012) - Kanthaphayao, Yutthana; Kamnarn, Uthen; Chunkag, Viboon
Abstract This paper presents the parallel operation control of a modular AC to DC converter via a serial communication bus. In the proposed system, multiple AC to DC converters are parallel‐connected at the output end for load current sharing. Each module of the AC to DC converter is controlled by its individual microcontroller. The microcontroller of each module is employed for the voltage control loop and communicates with the microcontrollers of the other converter modules. The RS485 serial communication is used to transmit information among the controllers, which checks the number of the converter module for calculating the input inductor current command of each converter module. Moreover, the clock signal is used for synchronization to prevent data collision on the serial communication bus. The proposed parallel operation control provides fast response when the converter module connects or disconnects according to the required power. The performance evaluation of the proposed system is conducted by simulation and experimental verification on two parallel isolated CUK converters. © 2012 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.